Hydro-energy cooperation in South Asia: prospects for transboundary energy and water security - Saklani, U.; Shrestha, P. P.; Mukherji, Aditi; Scott, Christopher A. (Elsevier, 2020)
The last decade has witnessed rapid progress in energy cooperation between the countries of the BBIN (Bangladesh, Bhutan, India and Nepal) sub-region. Cooperation has been bilateral, with each of the countries entering into separate energy development and trade agreement with India, broadly similar to the water sector where national governments engage bilaterally on transboundary cooperation and dispute resolution. A more recent wave of electrical grid interconnections and hydro-energy cooperation has emerged with governments increasingly shifting from bilateral to multilateral energy-sharing agreements. This trend holds considerable potential for regional transboundary water governance. Based on documentary and media analysis along with interviews of key BBIN policy-makers, we identify and examine in this paper four factors for future progress: 1) technical cooperation can be extended to information-sharing for policies and institutions to regulate and manage water resources; 2) India must seize the opportunities and benefits of enhanced regional leadership in the region; 3) simultaneous informal discussion and diplomatic negotiation of water, energy and their nexus can provide BBIN countries the opportunity to highlight potential gains of cooperation and interstate interdependencies; and 4) regional cooperation can give a strong impetus to nations for advancing structural reforms, building institutions and capacity, developing a shared knowledge base, bridging infrastructural gaps, attracting private sector participation, and addressing poverty alleviation goals including job creation.